The influence of encoding and testing directions on retrieval of spatial information in explored and described environments. Issue 1 (2nd January 2021) - Santoro, Ilaria; Sors, Fabrizio; Mingolo, Serena; Prpic, Valter; Grassi, Michele; Agostini, Tiziano; Murgia, Mauro
Abstract: The verbal descriptions of an environment elicit a spatial mental model, in which the linear disposition of the described objects might be related to the properties of the description. In particular the direction from which the environment is encoded might shape the spatial mental model, as a consequence of a cultural bias in reading and writing direction. The aim of the present study was to examine the influence of the direction in which objects are encoded on the retrieval of spatial information. In two experiments we asked participants to encode an environment through either physical exploration or verbal description, that are encoding modalities which preserve the sequential presentation of spatial information. We manipulated both the encoding and testing directions of the spatial information, and tested participants by using a two-alternative forced choice task. In both experiments, the results did not reveal any significant effect, disconfirming the idea of the left-right cultural bias for western people for this type of task. The lack of effect suggests that encoding an environment through physical movement and verbal descriptions determines the development of a mental representation which is relatively independent from encoding sequential order.